Low-water-permeability and high-PID-resistance EVA packaging adhesive film as well as preparation method and application thereof
By introducing GMA modified acrylate powder and heat-crosslinked EVA into the EVA packaging film for double curing, the problem of PID polarization in TOPCON battery cells was solved, and the effects of low water permeability and high PID resistance were achieved. Reduces production costs and maintains high light transmittance.
Patent Information
- Application Number
- CN202411371329.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-13
AI Technical Summary
When TOPCON battery cells use dual EVA packaging, polar VA groups cause sodium ions to migrate, resulting in charge enrichment and PID polarization and blackening, especially intensifying under the action of water vapor. The existing technology is difficult to effectively suppress PID phenomenon, and at the same time, it is introduced. Anti-PID additives increase production costs or affect light transmittance.
Introduce GMA modified acrylate powder and heat-crosslinked EVA for double curing, improve cross-linked network structure density, reduce water vapor transmission and block sodium ion migration, while maintaining light transmittance, and use appropriate cross-linking agents and additives In conjunction with the preparation of low-water permeability and high-resistance PID-type EVA encapsulation films.
The water vapor transmission rate is lower than 22gm/m2 and the power attenuation of PID components of 96h is less than 12.5%, while maintaining high light transmittance, reducing production costs, and improving insulation performance.
Smart Images

Figure BDA0005067660710000021 
Figure BDA0005067660710000071 
Figure BDA0005067660710000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of film packaging materials, and in particular relates to a low water permeability and high PID resistance type EVA packaging film and a preparation method and application thereof. Background Art
[0002] With the technological improvements of TOPCON cells and HJT cells in recent years, PERC cells have gradually faded out of the stage of the solar photovoltaic industry, while HJT cells are still in the trial development stage. With the continuous technical optimization, TOPCON cells have become the mainstream of the market since 2024. But as we all know, TOPCON cells are encapsulated with double EVA. The polar VA groups contained in EVA will induce the sodium ions in the glass to migrate to the passivation layer of the TOPCON cells, resulting in charge enrichment, which will cause the battery to produce PID (Potential Induced Degradation) polarization blackening phenomenon in the aging experiment. Especially under the action of water vapor, EVA resin will produce free acetic acid molecules, which will further induce the migration of sodium ions in the glass, resulting in the intensification of PID polarization. Therefore, in order to suppress the occurrence of PID polarization, the research and improvement of EVA photovoltaic film is of great significance to the promotion of the photovoltaic industry.
[0003] CN114605927A discloses a highly PID-resistant encapsulation film, a preparation method thereof, and a photovoltaic module. The cross-linked network of EVA and the added adamantane and fullerene form a conjugated network structure to cooperate with each other to block electron migration and improve the anti-PID ability. However, the introduction of fullerene and adamantane into the encapsulation film will increase the production cost, and the introduction of fullerene will reduce the transmittance and affect the power generation efficiency.
[0004] CN103923374A discloses an EVA film for reducing the PID phenomenon in photovoltaic modules and a preparation process thereof. By introducing N, N-di(2,6-diisopropylphenyl)carbodiimide anti-hydrolysis agent, the water barrier property of the packaging film is improved and its anti-PID ability is improved. However, the anti-hydrolysis agent contains a benzene ring, has poor UV resistance, and is prone to yellowing. It has a certain effect on water blocking, but cannot effectively prevent sodium ions in the glass from migrating to the battery cell, and there are certain safety hazards in the packaging of photovoltaic film modules.
[0005] Therefore, in view of the above technical problems, it is urgent to develop an EVA encapsulation film with low water vapor transmission rate and high PID resistance. Summary of the invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a low water permeability and high PID resistance type EVA packaging film and a preparation method and application thereof.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a low water permeability and high PID resistance type EVA encapsulation film, wherein the raw materials for preparing the low water permeability and high PID resistance type EVA encapsulation film include the following components in parts by weight:
[0009]
[0010] The EVA encapsulation film provided by the present invention introduces GMA (glycidyl methacrylate) modified acrylate powder, which can be dual-cured with heat-crosslinked EVA to improve the density of the crosslinked network structure. After curing, the light transmittance of EVA can still be maintained, and the water vapor permeability of the EVA film can be reduced, thereby blocking the migration of sodium ions in the front glass to the battery sheet, and further improving the occurrence of polarization-type PID blackening caused by the EVA film. In addition, the melting point of the GMA modified acrylate powder is close to that of EVA, the curing temperature is consistent, the processing is easy, the production cost is reduced, and the insulation performance is good.
[0011] In the present invention, the low water permeability refers to the water vapor permeability of the EVA encapsulation film being lower than 22 gm / m 2 ; High PID resistance means that the power attenuation of the front side of the PID component is less than 12.5% after 96 hours, and the power attenuation of the back side of the PID component is less than 11.2% after 96 hours.
[0012] In the present invention, the raw materials for preparing the low water permeability and high PID resistance EVA encapsulation film are calculated by weight, and the amount of ethylene-vinyl acetate copolymer used can be 80 parts by weight, 82 parts by weight, 84 parts by weight, 86 parts by weight, 88 parts by weight, 90 parts by weight, 92 parts by weight, 94 parts by weight, 96 parts by weight, 98 parts by weight or 100 parts by weight, etc., but are not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0013] In the present invention, the raw materials for preparing the low water permeability and high PID resistance EVA encapsulation film are calculated by weight, and the amount of GMA modified acrylate powder used can be 0.3 weight parts, 0.5 weight parts, 1.0 weight parts, 2.0 weight parts, 4.0 weight parts, 6.0 weight parts, 8.0 weight parts, 10 weight parts, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] In the present invention, the raw materials for preparing the low water permeability and high PID resistance EVA encapsulation film are calculated by weight, and the amount of the main cross-linking agent used can be 0.3 weight part, 0.5 weight part, 0.7 weight part, 0.8 weight part, 0.9 weight part, 1.0 weight part, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] In the present invention, the raw materials for preparing the low water permeability and high PID resistance EVA encapsulation film are calculated by weight, and the amount of the auxiliary cross-linking agent used can be 0.5 weight parts, 0.6 weight parts, 0.8 weight parts, 0.9 weight parts, 1.1 weight parts, 1.3 weight parts, 1.5 weight parts, etc., but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] In the present invention, the raw materials for preparing the low water permeability and high PID resistance EVA encapsulation film are calculated in parts by weight, and the amount of the auxiliary agent used can be 0.3 parts by weight, 0.5 parts by weight, 0.6 parts by weight, 0.8 parts by weight, 0.9 parts by weight, 1.1 parts by weight, 1.3 parts by weight, 1.5 parts by weight, 2 parts by weight, etc., but are not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0017] Preferably, the melting point of the ethylene-vinyl acetate copolymer is 60-80°C, for example 60°C, 63°C, 65°C, 68°C, 70°C, 73°C, 75°C, 78°C, 80°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Preferably, the molar content of VA in the ethylene-vinyl acetate copolymer is 15-30%, for example 15%, 18%, 20%, 23%, 25%, 28%, 30%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the melt flow rate of the ethylene-vinyl acetate copolymer at 190°C is 5-30 g / 10min, for example 5 g / 10min, 8 g / 10min, 10 g / 10min, 13 g / 10min, 15 g / 10min, 18 g / 10min, 20 g / 10min, 23 g / 10min, 25 g / 10min, 28 g / 10min, 30 g / 10min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0020] Preferably, the particle size of the GMA modified acrylate powder is 1-20 microns, for example, 1 micron, 2 microns, 3 microns, 4 microns, 5 microns, 6 microns, 7 microns, 8 microns, 9 microns, 10 microns, 11 microns, 12 microns, 13 microns, 14 microns, 15 microns, 16 microns, 17 microns, 18 microns, 19 microns, 20 microns, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, the melting point of the GMA modified acrylate powder is 60-80°C, for example 60°C, 63°C, 65°C, 68°C, 70°C, 73°C, 75°C, 78°C, 80°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] Preferably, the thermal curing temperature of the GMA modified acrylate powder is 130-155°C, for example 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] Preferably, the primary cross-linking agent is an organic peroxide cross-linking agent.
[0024] Preferably, the organic peroxide crosslinking agent includes any one of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexanoate, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxyacetate, tert-butyl peroxyisobutyrate or tert-amyl peroxyisobutyrate, or a combination of at least two thereof.
[0025] Preferably, the auxiliary cross-linking agent includes any one of triallyl isocyanurate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, methyl trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, and pentaerythritol tetraacrylate, or a combination of at least two thereof.
[0026] Preferably, the auxiliary agent includes any one of a silane coupling agent, an antioxidant, and a light stabilizer, or a combination of at least two of them.
[0027] Preferably, the auxiliary agent includes 0.1-1.0 parts by weight of a silane coupling agent (e.g., 0.1 parts by weight, 0.3 parts by weight, 0.5 parts by weight, 0.8 parts by weight, 1.0 parts by weight, etc.), 0.1-0.5 parts by weight of an antioxidant (e.g., 0.1 parts by weight, 0.2 parts by weight, 0.4 parts by weight, 0.5 parts by weight, etc.), and 0.1-0.5 parts by weight of a light stabilizer (e.g., 0.1 parts by weight, 0.2 parts by weight, 0.4 parts by weight, 0.5 parts by weight, etc.).
[0028] Preferably, the silane coupling agent includes any one of vinyltrimethoxysilane, vinyltriethoxysilane, dodecyltriethoxysilane, octyltriethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(methacryloxypropyl)trimethoxysilane or vinyltri(2-methoxyethoxy)silane, or a combination of at least two thereof.
[0029] Preferably, the antioxidant includes any one of antioxidant 1076, antioxidant 168, antioxidant 264 or antioxidant 1010, or a combination of at least two thereof, preferably antioxidant 1076.
[0030] Preferably, the light stabilizer includes any one of the light stabilizer 770 , the light stabilizer 622 , the light stabilizer 944 , the light stabilizer 1084 or the light stabilizer 783 , or a combination of at least two of them.
[0031] In a second aspect, the present invention provides a method for preparing the low water permeability and high PID resistance type EVA packaging film as described in the first aspect, the preparation method comprising the following steps:
[0032] Ethylene-vinyl acetate copolymer, GMA modified acrylate powder, main cross-linking agent, auxiliary cross-linking agent and auxiliary agent are mixed, and then put into a casting machine, and through hot-melt extrusion, stretching, pulling and winding, the low water permeability and high PID resistance EVA packaging film is obtained.
[0033] Preferably, the mixing is carried out in a mixer.
[0034] Preferably, the temperature of the hot melt extrusion is 80-110°C, for example 80°C, 85°C, 90°C, 95°C, 100°C, 105°C or 110°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the thickness of the low water permeability and high PID resistance EVA encapsulation film is 300-600 μm, for example, 300 μm, 320 μm, 340 μm, 350 μm, 380 μm, 400 μm, 420 μm, 440 μm, 450 μm, 470 μm, 480 μm, 500 μm, 520 μm, 540 μm, 550 μm, 580 μm, 600 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 380-500 μm.
[0036] In a third aspect, the present invention provides an application of the low water permeability and high PID resistance type EVA packaging film as described in the first aspect in the packaging of TOPCON cell photovoltaic double-glass modules.
[0037] Compared with the prior art, the present invention has at least the following beneficial effects:
[0038] (1) The EVA encapsulation film provided by the present invention introduces GMA modified acrylate powder, which can be dual-cured with heat-crosslinked EVA to improve the density of the crosslinked network structure. After curing, the light transmittance of EVA can still be maintained, and at the same time, the water vapor permeability of the EVA film can be reduced, blocking the migration of sodium ions in the front glass to the battery cell, and further improving the occurrence of polarization-type PID blackening caused by the EVA film; in addition, the melting point of the GMA modified acrylate powder is close to that of EVA, the curing temperature is consistent, it is easy to process, the production cost is reduced, and the insulation performance is good;
[0039] (2) Specifically, the low water permeability and high PID resistance type EVA encapsulation film provided by the present invention has a light transmittance of ≥90% after cross-linking, and a water vapor transmission rate of 9-22 gm / m 2 , PID 96h are qualified. DETAILED DESCRIPTION
[0040] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0041] Unless otherwise specified, some of the raw material information used in the examples and comparative examples of the present invention is shown in the following table; other raw materials not listed, unless otherwise specified, can be purchased commercially or prepared according to conventional methods in the art:
[0042] Brand Ethylene-vinyl acetate copolymer Yanshan Petrochemical EVA20F20 GMA modified acrylate powder Akzobel INTERPON A2200 Polycarbodiimide Keshengtong BIO-362 Polyacrylamide French Aisen AN926SH
[0043] Examples 1 to 6
[0044] A low water permeability and high PID resistance type EVA encapsulation film, the components in the raw materials for its preparation are shown in Table 1, and the units of the components in Table 1 are all "parts by weight".
[0045] Table 1
[0046]
[0047] The preparation method of the EVA encapsulation film provided in Examples 1 to 6 includes: uniformly mixing ethylene-vinyl acetate copolymer, GMA modified acrylate powder, primary cross-linking agent, auxiliary cross-linking agent, silane coupling agent, antioxidant and light stabilizer through a mixer, and then putting them into a casting machine, and undergoing hot melt extrusion (temperature of 95°C), stretching, pulling and winding to obtain the low water permeability and high PID resistance EVA encapsulation film.
[0048] Comparative Examples 1 to 6
[0049] An EVA encapsulation film, the components in the raw materials for its preparation are shown in Table 2, and the units of the components in Table 2 are all "parts by weight".
[0050] Table 2
[0051]
[0052] The EVA encapsulation films provided in the embodiment and the comparative example are respectively assembled into double-glass components, and the method is as follows:
[0053] 1) Solar cell module packaging structure: glass + EVA film + Jietai LECO-TOPCON battery cell + EVA film + glass, where the glass is 2mm rolled glass; the thickness of the EVA film is 500μm; the battery cell is 182*72 standard Jietai LECO-TOPCON battery cell with a thickness of about 130μm.
[0054] 2) Lamination conditions: 145°C, vacuum time 5 min, lamination time 10 min.
[0055] The above double-glass components were tested as follows:
[0056] (1) Light transmittance: Tested in accordance with GB / T 29848-2018;
[0057] (2) Water vapor transmission rate: Tested in accordance with the national standard GB / T 26253-2010;
[0058] (3) Photovoltaic EL (electroluminescence) image appearance: tested in accordance with IEC60904-2;
[0059] (4) Anti-PID performance: tested in accordance with standard IEC61215-2020.
[0060] The performance test results are shown in Table 3.
[0061] Table 3
[0062]
[0063]
[0064] It can be seen from Table 3 that the EVA encapsulation films provided in the embodiments of the present invention have good anti-PID performance (96h front power attenuation of PID component: -2.35% to -12.5%, 96h back power attenuation of PID component: -1.21% to -11.2%) and low water vapor transmission rate (9 to 22 gm / m 2 ), and the transmittance meets the requirement of >90%.
[0065] Compared with Example 1, the preparation raw materials of the EVA encapsulation films provided in Comparative Examples 1 to 3 do not contain GMA modified acrylate powder, but introduce anti-PID additives. It can be seen that the anti-PID effects are all poor. This is because the anti-PID additive cannot form a continuous phase in the EVA polymer chain segment to effectively block the migration of sodium ions in the glass, and zirconium phosphate is added in Comparative Example 1, and the light transmittance of the film is low; while in Comparative Example 4, no anti-PID additive and GMA modified acrylate powder are added, and the water vapor permeability and anti-PID performance of the film are relatively poor; in Comparative Example 5, due to the excessive amount of GMA modified acrylate powder added, the light transmittance of the film cannot meet the requirements; in Comparative Example 6, the GMA modified acrylate powder is replaced with an equal amount of GMA, and the anti-PID performance of the EVA encapsulation film decreases.
[0066] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the low water permeability and high PID resistance type EVA encapsulation film and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A low water permeability and high PID resistance type EVA packaging film, characterized in that: The raw materials for preparing the low water permeability and high PID resistance type EVA encapsulation film include the following components in parts by weight:
2. The low water permeability and high PID resistance type EVA packaging film according to claim 1, characterized in that: The melting point of the ethylene-vinyl acetate copolymer is 60-80°C; Preferably, the molar content of VA in the ethylene-vinyl acetate copolymer is 15-30%; Preferably, the melt flow rate of the ethylene-vinyl acetate copolymer at 190° C. is 5-30 g / 10 min.
3. The low water permeability and high PID resistance type EVA packaging film according to claim 1 or 2, characterized in that: The particle size of the GMA modified acrylate micropowder is 1-20 microns; Preferably, the melting point of the GMA modified acrylate micropowder is 60-80°C; Preferably, the thermal curing temperature of the GMA modified acrylate micropowder is 130-155°C.
4. The low water permeability and high PID resistance type EVA packaging film according to any one of claims 1 to 3, characterized in that: The main cross-linking agent is an organic peroxide cross-linking agent; Preferably, the organic peroxide crosslinking agent includes any one of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexanoate, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxyacetate, tert-butyl peroxyisobutyrate or tert-amyl peroxyisobutyrate, or a combination of at least two thereof.
5. The low water permeability and high PID resistance type EVA packaging film according to any one of claims 1 to 4, characterized in that: The auxiliary crosslinking agent includes any one of triallyl isocyanurate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, methyl trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, and pentaerythritol tetraacrylate, or a combination of at least two thereof.
6. The low water permeability and high PID resistance type EVA packaging film according to any one of claims 1 to 5, characterized in that: The auxiliary agent includes any one of a silane coupling agent, an antioxidant, and a light stabilizer, or a combination of at least two thereof; Preferably, the auxiliary agent includes 0.1-1.0 parts by weight of a silane coupling agent, 0.1-0.5 parts by weight of an antioxidant, and 0.1-0.5 parts by weight of a light stabilizer.
7. The low water permeability and high PID resistance type EVA packaging film according to claim 6, characterized in that: The silane coupling agent includes any one of vinyl trimethoxy silane, vinyl triethoxy silane, dodecyl triethoxy silane, octyl triethoxy silane, 3-(2,3-epoxypropoxy) propyl trimethoxy silane, 3-(methacryloxypropyl) trimethoxy silane or vinyl tris (2-methoxyethoxy) silane or a combination of at least two thereof; Preferably, the antioxidant comprises any one of antioxidant 1076, antioxidant 168, antioxidant 264 or antioxidant 1010 or a combination of at least two thereof, preferably antioxidant 1076; Preferably, the light stabilizer includes any one of the light stabilizer 770 , the light stabilizer 622 , the light stabilizer 944 , the light stabilizer 1084 or the light stabilizer 783 , or a combination of at least two of them.
8. A method for preparing a low water permeability and high PID resistance type EVA packaging film as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: Ethylene-vinyl acetate copolymer, GMA modified acrylate powder, main cross-linking agent, auxiliary cross-linking agent and auxiliary agent are mixed, and then put into a casting machine, and through hot-melt extrusion, stretching, pulling and winding, the low water permeability and high PID resistance EVA packaging film is obtained.
9. The preparation method according to claim 8, characterized in that: The mixing is carried out in a mixer; Preferably, the temperature of the hot melt extrusion is 80-110°C; Preferably, the thickness of the low water permeability and high PID resistance type EVA packaging film is 300-600 μm, preferably 380-500 μm.
10. Use of the low water permeability and high PID resistance EVA packaging film as claimed in any one of claims 1 to 7 in the packaging of TOPCON cell photovoltaic double-glass modules.
Citation Information
Cited By
EPE type three-layer co-extrusion adhesive film as well as preparation method and application thereof
CN119752345A
